HUBUNGAN PENGGUNAAN VENTILATOR MEKANIK TERHADAP KEJADIAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) - Panjaitan, Devi K; Sinatra, Jadeny; Siahaan, Dwi L (Jurnal Kedokteran Methodist, 2021)
Background: VAP is pneumonia due to the use of a mechanical ventilator for more than 2 days in   the ICU. VAP mortality rates generally range from 25% - 50% but in some cases have increased to 70%. The aim of this study was to see whether there was a relationship between the use of a mechanical ventilator on the incidence of VAP. Method : This study was conducted using a literature review technique. Result: From 15 research many research results that are in line, and state that there is a relationship between the use of mechanical ventilators with risk factors for prolonged use of mechanical ventilators, age, COPD, decreased consciousness, and invasive surgery on VAP, thereby increasing the mortality of VAP events. Conclusion: The use of mechanical ventilators has a relationship with the occurrence of VAP, with duration of mechanical ventilator use, age, COPD, decreased consciousness, and invasive surgery as risk factor indicators.